2021
DOI: 10.1007/s11920-021-01279-z
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for Child Mental Health Raised by School Closure and Home Confinement During the COVID-19 Pandemic

Abstract: Purpose of Review The closure of schools during the COVID-19 pandemic has interrupted the education of children worldwide. This paper reviews the psychological effects of this action on children and the impact on school-based services. Recent Findings Emerging epidemiologic findings have generated an intense debate about the need for, and potential benefit of, school closure in the context of COVID-19. International research reveals reactions in children that are not ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 48 publications
1
27
0
10
Order By: Relevance
“…COVID-19 has instilled fear in children because they are worried about becoming sick and their parents having to stay home from work (12). Furthermore, changes in family economic conditions, protective confinement, social isolation, and deaths of loved ones have had varying degrees of effect on children's mental health (13)(14)(15). Therefore, innovative approaches that increase access to mental health services and promote resilience and mental well-being, such as maintaining social connections despite the isolation and renewing social ties during the recovery phase, should be explored.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 has instilled fear in children because they are worried about becoming sick and their parents having to stay home from work (12). Furthermore, changes in family economic conditions, protective confinement, social isolation, and deaths of loved ones have had varying degrees of effect on children's mental health (13)(14)(15). Therefore, innovative approaches that increase access to mental health services and promote resilience and mental well-being, such as maintaining social connections despite the isolation and renewing social ties during the recovery phase, should be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Digital learning requires adequate technical equipment and digital competency, but social inequalities have been be observed [27,28]. Helm et al [15] reported that a higher socioeconomic background increased the quality of technical equipment and digital literacy.…”
Section: Digital Learningmentioning
confidence: 99%
“…Hal tersebut ditandai dengan 46 peserta didik 76,7% nya selalu membantu keluarga di rumah, dengan demikian anak dan orang tua akan dapat bersosialisasi dengan baik sehingga hubungan keluarga akan terjalin dengan harmonis. Permaslahan tersebut sejalan dengan (Prfefferbaum, 2021) berdasarkan datanya pandemi membuat orang tua dan anak memiliki waktu yang lebih banyak sehingga hal tersebut dapat dimanfaatkan untuk membangun hubungan keluarga yang baik dan harmonis.…”
Section: Perkembangan Psikososial Peserta Didik DI Masa Pandemiunclassified